STATIC OF ORTHODONTIC APPLIANCES WITH MOVABLE INCLINED PLANE FOR MESIAL BATE TREATMENT - P.S. Flis; A.I. Hryhorenko; N.M. Doroshenko; M.M. Tormakhov; V.V. Filonenko (Ukrainian Medical Stomatological Academy, 2016)
Urgency of an issue. An orthodontic appliance with a movable inclined plane, which consists of a plastic base, vestibular arc, retaining clasps and inclined plane, connected with the base via two clubshaped springs (torsion springs) was proposed. Creation and introduction of new treatment technologies into medical practice requires its mechanics and mathematical background. The aim of the research. Mechanics and mathematical modeling of functionally directing appliance with a movable inclined plane static work for improving sagittal dentoalveolar anomalies and deformations treatment methods. Materials and methods. Maxillodental patient's static was modeled by the methods of theoretical mechanics during the treatment of mesial occlusion with the appliance with a movable inclined plane. The study used parameters: the angle of the inclined plane of the appliance, the size of the facial skeleton, axial angle of the anterior teeth inclination, the coefficient of friction between the inclined plane and the patient's teeth. Two types of clubshaped springs (torsion springs) was studied: 1 - the one, which create a cushioning effect of the inclined plane action, but do not change its angle of inclination (passive); 2 - one, that seek to increase the angle of the plane inclination due to the disclosure of the curl (active). Results and discussion. Orthodontic forces occurring in the dentoalveolar complex while using orthodontic appliances can be decomposed into two components: the force acting along the axis of the tooth Q, and the force directed perpendicular to this axis direction P. The force Q progressively moves the frontal teeth in the axial direction, and the force P translational-rotationally in the vestibular direction. By setting different angles of inclined plane inclination β, the forces P and Q can be changed, changing the position of the frontal teeth and the alveolar process. The angle of the tooth axis inclination at the beginning of treatment α is determined by the anatomical characteristics of the patient and can take on values in the range 45-75°. Since the orthodontic force vector is in vestibular direction, the angle β is in the range from -30° to α. Minimum orthodontic force will occur in the case where the angle between the inclined plane and a line connecting a point that represents the center of the articular head of the temporomandibular joint, and the incisors contact point will be equal to the arctangent of the coefficient of friction between the patient's teeth and the inclined plane. Based on the orthodontic forces calculations results, the force P increases and Q force decreases with increasing of angle β. The angle between the inclined plane and the axis of the frontal teeth (α - β) influences the ratio between P and Q. If (α - β) < 45° the forces P exceeds the force Q, if (α - β) = 45°, then P = Q, and if (α - β) > 45° the forces P will be less then forces Q. Ratio P < Q is not eligible, since the inclination of the tooth must prevail over its intrusion. About 30° is the most preferred angle between the inclined plane and the axis of the frontal teeth. Conclusion. The presence of elastic joints in functional-directing appliences with an inclined plane, which is used as clubshaped spring, allows us to change vehicles rigidity and to provide more stable support of orthodontic force during the treatment. The movable inclined plane with active springs acts on the teeth not only during the act of swallowing, but in a state of physiological dormancy also.